2020
DOI: 10.1136/lupus-2020-000418
|View full text |Cite
|
Sign up to set email alerts
|

Lupus serum induces inflammatory interaction with neutrophils in human glomerular endothelial cells

Abstract: ObjectivesSLE is associated with endothelial cell dysfunction (ECD). Understanding how ECD leads to neutrophil infiltration into glomeruli is essential to finding therapeutic targets for SLE. The aim of this study is to determine the effect of SLE serum from patients with active disease to induce neutrophil adhesion to and chemotaxis towards glomerular endothelial cells and factors induced by serum that associate with neutrophil chemotaxis.MethodsPatients with SLE had serum collected during paired longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Neutrophils from SLE patients in active flare often produce lower levels of ROS in vitro than those with inactive disease, possibly due to exhaustion of the neutrophils in vivo ( 76 ), or lower expression of Fcγ and complement receptors ( 82 ). As yet unidentified factors within SLE serum induce production of cytokines by human renal glomerular endothelial cells which promote neutrophil chemotaxis and adhesion ( 83 ). In patients with lupus nephritis, immune complexes become deposited within tissues in the kidney ( 6 ).…”
Section: Ros Mediated Tissue Damagementioning
confidence: 99%
“…Neutrophils from SLE patients in active flare often produce lower levels of ROS in vitro than those with inactive disease, possibly due to exhaustion of the neutrophils in vivo ( 76 ), or lower expression of Fcγ and complement receptors ( 82 ). As yet unidentified factors within SLE serum induce production of cytokines by human renal glomerular endothelial cells which promote neutrophil chemotaxis and adhesion ( 83 ). In patients with lupus nephritis, immune complexes become deposited within tissues in the kidney ( 6 ).…”
Section: Ros Mediated Tissue Damagementioning
confidence: 99%
“…Few studies have examined the relationship between ERS and endothelial dysfunction in the LN [ 119 ]. Russell et al [ 120 ] and Oates et al [ 121 ] found that human glomerular endothelial cells in SLE-induced neutrophil chemotaxis and adhesion and further aggravated glomerular lesions through ERS and oxidative stress pathways.…”
Section: Ers In Renal Resident Cells In Lnmentioning
confidence: 99%
“…Increased circulating apoptotic endothelial cells and decreased bone marrow-derived endothelial progenitor cells and myeloid angiogenic cells suggests an imbalance between endothelial cell injury and repair in SLE and LN patients ( 73 ). Stimulation of glomerular endothelial cells with serum from SLE and LN patients increases IL-1β and IL-6 transcripts and IL-8, IL-15 and PDGF-BB secretion and is associated with increased neutrophil recruitment ( 75 , 76 ). These pro-inflammatory mediators also induce glycocalyx shedding.…”
Section: Endothelial Injury In Lupus Nephritismentioning
confidence: 99%